FISCAL POLICY IN BOSNIA AND HERZEGOVINA - AN INSTRUMENT FOR FASTER GROWTH OR ECONOMIC STAGNATION? - Faruk Hadžić; Nebojša Savanović (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
The paper investigates the impact of fiscal policy on economic growth, foreign direct investment and employment in Bosnia and Herzegovina. The focus of research is fiscal policy, which as a lever of economic policy that affects economic growth and development. The aim of the research is to determine the impact of fiscal policy on the economy of Bosnia and Herzegovina and propose solutions for higher growth and development, a higher degree of foreign direct investment and reducing the unemployment rate. The results of the research show that the fiscal policy for the years that are the subject of the research, has affected the public debt of the state. High taxes and contributions have contributed to the spread of the gray economy, fiscal discipline is at a low level due to the management in this way of this lever of economic policy. Public financial management should be one of the key macroeconomic goals, with special emphasis on fiscal policy. The research went in the direction of analyzing current trends and proposals for improving the situation. The research aims to show the current statistical impact of variables on gross domestic product, on growth and development and the impact after the application of expansionary fiscal policy on the same variables. It is recommended that economic policy be conducted in the direction of releasing additional funds through the redistribution of taxes in favor of workers, in the direction of capital investments that will repay themselves, to reduce the rate of taxes and contributions on wages and with incentives for investors, to go towards stimulating production and tax reliefs for export-oriented activities with an effort to try to produce products whose production is possible in our conditions, and all this is mostly possible with the implementation of an expansive fiscal policy.
Keywords: Macroeconomics, Fiscal Policy, GDP, Public Expenditure, Investments